MORPHOMETRIC ANALYSIS OF TRUMPET SHELL, CHARONITA TRITONIS, (LITTORINIMORPHA: RANELLIDAE) FROM SARANGANI PROVINCE, PHILIPPINES - Ramas, Cristina; Rosales, Raamah C; Rosales, Maria Eden (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2024)
The C. tritonis is an important biological indicator in coral reef ecosystem. Conservation of the species is essential to maintain the integrity of the reef. This study was conducted to investigate variations on the morphometric characters on Trumpet shell, Charonia tritonis Linneaus 1758, to elucidate shell developmental history. A total of 50 shells were measured for length and weight for morphometric analysis. The result on allometric relationships indicated that during the shell’s development, the increase in aperture length was not proportional to the increase of the shell width. However, the increase in aperture length was significantly related to the increase in weight and total shell length. These variations on morphometric relationships could possibly be attributed to the movement and feeding behavior of the organism. The continued pressure of the foot muscle as it extends while moving and feeding pushed the aperture length causing it to increase in length. It is recommended for further study to include other landmark variations of the trumpet shell such as shell spire and body whorl for deeper understanding on shell developmental biology.